Association between maternal plasma ferritin concentration, iron supplement use, and the risk of gestational diabetes: a prospective cohort study. Issue 3 (21st May 2021) - Zhang, Xu; Wu, Meng; Zhong, Chunrong; Huang, Li; Zhang, Yu; Chen, Renjuan; Zhou, Xuezhen; Xu, Shangzhi; Li, Qian; Cui, Wenli; Wang, Xiaoyi; Chen, Xi; et al.
ABSTRACT: Background: The association between iron supplementation and gestational diabetes mellitus (GDM) is still inconclusive, and this association has not been extensively studied in relation to plasma ferritin in the early second trimester. Objectives: We aimed to prospectively examine the independent and combined associations of plasma ferritin concentrations and iron supplement use with GDM. Methods: We studied 2117 women from the Tongji Maternal and Child Health Cohort in Wuhan, China. Plasma ferritin around 16 weeks' gestation was measured by ELISA kits and information on iron supplement use was collected by questionnaires. GDM was diagnosed by a 75-g oral-glucose-tolerance test (OGTT) at 24–28 weeks' gestation. A log-Poisson regression model was used to estimate the RR of GDM associated with plasma ferritin and iron supplementation. Results: The median and IQR of plasma ferritin was 52.1 (29.6–89.9) ng/mL, and 863 (40.8%) participants reported use of iron supplements during the second trimester. A total of 219 (10.3%) participants developed GDM. Adjusted RRs (95% CIs) for GDM across increasing quartiles of plasma ferritin were 1.00 (reference), 2.14 (1.37, 3.34), 2.03 (1.30, 3.19), and 2.72 (1.76, 4.21), respectively. After adjustment, supplemental iron ≥60 mg/d during the second trimester was associated with an increased risk of GDM compared with nonusers (RR: 1.37; 95% CI: 1.02, 1.84). Conclusions: Both elevated plasma ferritin concentrations in the early second trimester and use of ≥60 mg/d of supplemental iron during pregnancy are independently associated with increased risk of GDM. Further clinical trials with precision nutrition approaches considering both baseline iron status and supplement use are needed to evaluate the benefits and risks of iron supplementation during pregnancy.